IMPLEMENTASI PEMBERDAYAAN MELALUI BUDIDAYA IKAN NILA MELALUI EKSTENSIF PLUS MASA PANDEMI COVID-19 DI PAGESANGAN KOTA MATARAM - Ibrahim Ibrahim; Burhanuddin Burhanuddin; M. Saleh; M Sobry; Akhmad Syafruddin; Salahuddin Salahuddin (Universitas Gajah Putih, Indonesia, 2022)
The poverty level of the community is still high in the Pagesangan Village, Mataram District, Mataram City during the Covid-19 pandemic. The purpose of this community service activity is to analyze the implementation of empowerment through extensive tilapia cultivation during the COVID-19 pandemic at Pagesangan, Mataram City. The method of implementing this community service activity is through assistance in the form of practice in the community. The results of this community service activity are motivation and life changes, especially the level of welfare and income. Activities are able to provide a sustainable livelihood. Cultivators have been successfully carried out independently as an aspect of self-development and preparation during the COVID-19 pandemic. The success of this activity is a form of livelihood strategy during the Covid-19 pandemic.